Flexibility mindsets: Reducing biases that result from spontaneous processing. Issue 1 (2nd January 2022) - Sassenberg, Kai; Winter, Kevin; Becker, Daniela; Ditrich, Lara; Scholl, Annika; Moskowitz, Gordon B.
ABSTRACT: Spontaneous (i.e., heuristic, fast, effortless, and associative) processing has clear advantages for human cognition, but it can also elicit undesirable outcomes such as stereotyping and other biases. In the current article, we argue that biased judgements and behaviour that result from spontaneous processing can be reduced by activating various flexibility mindsets . These mindsets are characterised by the consideration of alternatives beyond one's spontaneous thoughts and behaviours and could, thus, contribute to bias reduction. Research has demonstrated that eliciting flexibility mindsets via goal and cognitive conflicts, counterfactual thinking, , recalling own past flexible thoughts or behaviour, and adopting a promotion focus reduces biases in judgements and behaviour. We summarise evidence for the effectiveness of flexibility mindsets across a wide variety of important phenomena – including creative performance, stereotyping and prejudice, interpersonal behaviour, and decision-making. Finally, we discuss the underlying processes and potential boundary conditions.